Exploring the potentials and horizons of network block device (NBD) integration on the android ecosystem - Rahman, Tanvir; Ahmed, Tanjid; Rahman, Md. Sakibur; Hossain, Amreen (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.